Thai Entrepreneurs under the New Competition in Tourism Business: Case Study of Chiang Mai Province - Yamthap, Sunanta; Limpiti, Sasikarn; al., et (Journal of Thai Hospitality and Tourism, 2022)
During the past five years, there has been an increasing number of Chinese tourists visiting Thailand, but Chinese businesses and entrepreneurs have been trying to open their tourism-related businesses in Thailand for economic purposes. The situation has caused emerging challenges for Thailand’s local entrepreneurs who have been conducting their tourism-related businesses. This article studies the impact of Chinese influence, specifically regarding Chinese businesses toward Thai entrepreneurs and their tourism-related businesses in the booming Chinese tourism market context. The field site is in Chiang Mai. We applied social sciences research and qualitative methods, collecting information during 2017–2018 from two sources: relevant documents and group interviews in five particular business sections: hotel and accommodation, wellness-spa and massage, travel agency, tourism-orientated business, and tourism-orientated professionals. The findings are relevant to the emerging challenges of Chinese competitors in the Thai tourism market. Thai businesses in five sections have been impacted differently by the findings. However, each business has attempted to adapt diversely, depending on its capital, networks, and knowledge. We also found that tourism-related business in Chiang Mai could not be solved successfully if better, more organized systems were not adopted. The efficient incorporation among relevant stakeholders, authorities, and civil society to build a mutually beneficial and long-term, sustainable market is the ideal goal moving into the future.